2012
DOI: 10.7314/apjcp.2012.13.1.349
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Codon 72 Polymorphism and Risk of Acute Leukemia

Abstract: TP53 is the mostly commonly mutated gene in many cancers and the P53 tumor suppressor protein is involved in multiple cellular processes, including transcription, DNA repair, genomic stability, senescence, cell cycle control and apoptosis. A common single nucleotide polymorphism located within the proline rich region of TP53 gene at codon 72 in exon 4 encodes either proline or arginine. TP53 Arg 72 is more active than TP53 Pro 72 in inducing apoptosis. The aim of this study was to understand the association of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
1
18
1
1
Order By: Relevance
“…We found no evidence to support variation at TP53 codon 72 as an independent determinant of de novo AML risk and survival. We could not confirm an association of TP53Arg72 with AML, as shown Dunna et al (), who used, blood samples for genotyping, but timing of collection, i.e. diagnosis or remission, was not stated.…”
Section: Distribution and Odds Ratios Of Tp53 Pro72arg Genotypes In Cmentioning
confidence: 66%
See 1 more Smart Citation
“…We found no evidence to support variation at TP53 codon 72 as an independent determinant of de novo AML risk and survival. We could not confirm an association of TP53Arg72 with AML, as shown Dunna et al (), who used, blood samples for genotyping, but timing of collection, i.e. diagnosis or remission, was not stated.…”
Section: Distribution and Odds Ratios Of Tp53 Pro72arg Genotypes In Cmentioning
confidence: 66%
“…In de novo AML, results of such studies are hampered by small subject numbers, not providing Hardy–Weinberg equilibrium (HWE), confounding different leukaemia subentities or by selection of inappropriate source materials for genotyping (Ruan et al , ). A case–control study from India, of 141 AML patients and 245 controls, using unspecified blood samples for genotyping showed a significant association of homozygous TP53Arg72 with AML susceptibility [odds ratio (OR) 1·75, 95% confidence interval (CI) 1·14–2·67] (Dunna et al , ). The largest case–control study in AML to date from China using 307 diagnostic bone marrow samples for genotyping and 560 controls showed significantly inferior treatment outcomes in homozygous TP53Arg72 carriers [2‐year overall survival (OS) Pro/Pro and Pro/Arg 45·7% vs. Arg/Arg 16·5%, P = 0·003] but no association with AML development (Shi et al , ).…”
Section: Distribution and Odds Ratios Of Tp53 Pro72arg Genotypes In Cmentioning
confidence: 99%
“…The frequency of the homozygous Arginine genotype was significantly elevated in the AML group compared to the control group [5].…”
Section: Oral Anaerobic Bacteria and Acute Myeloid Leukemiamentioning
confidence: 87%
“…It has been observed that the codon 72 polymorphism of p53 has been significantly associated with AML cases compared to controls [5]. The frequency of the homozygous Arginine genotype was significantly elevated in the AML group compared to the control group [5].…”
Section: Oral Anaerobic Bacteria and Acute Myeloid Leukemiamentioning
confidence: 90%
“…In de novo AML, results of such studies are hampered by small subject numbers, not providing Hardy-Weinberg equilibrium (HWE), confounding different leukaemia subentities or by selection of inappropriate source materials for genotyping (Ruan et al, 2015). A case-control study from India, of 141 AML patients and 245 controls, using unspecified blood samples for genotyping showed a significant association of homozygous TP53Arg72 with AML susceptibility [odds ratio (OR) 1Á75, 95% confidence interval (CI) 1Á14-2Á67] (Dunna et al, 2012). The largest case-control study in AML to date from China using 307 diagnostic bone marrow samples for genotyping and 560 controls showed significantly inferior treatment outcomes in homozygous TP53Arg72 carriers [2-year overall survival (OS) Pro/Pro and Pro/Arg 45Á7% vs. Arg/Arg 16Á5%, P = 0Á003] but no association with AML development (Shi et al, 2011).…”
mentioning
confidence: 99%